Cloud of assets and threats: A playful method to raise awareness for cloud security in industry - Zhao, T.; Lechner, U.; Pinto-Albuquerque, M.; Ata, E. (OpenAccess Series in Informatics, 2022)
Cloud computing has become a convenient technology widely used in industry, providing profit and flexibility to companies. Many enterprises embrace cloud service by migrating their products and solutions from on-premise to cloud environments. Cloud assets and applications are vulnerable to security challenges if not adequately protected. Regulations, standards and guidelines aim to enforce cloud security controls in the industry and practitioners need training to raise awareness of cloud security issues and learn about the defense mechanisms and controls. We propose a serious game Cloud of Assets and Threats (CAT) for enhancing cloud security awareness of industrial practitioners. This study extends first results of applying such a serious game in industry [25] and refines its design in two iterations. In the first design iteration, we implemented a digital game platform with six attack scenarios and developed a new player versus environment gaming mode. In the second design iteration, we adjusted the attack scenarios and introduced different difficulty levels for the scenarios. We present, analyse, and discuss the game events. We conclude that CAT is a promising method to raise awareness for cloud security in the industry.